Preoperative Fibrosis-4 (FIB-4) Evaluation May Be Helpful to Evaluate Prognosis of Gastric Cancer Patients Undergoing Operation: A Retrospective Study - Xu, Ke; Shi, Mingming; Zhang, Weiteng; Shi, Yiyi; Dong, Qiantong; Shen, Xian; Chen, Xiaolei; Lin, Ji (Frontiers in Oncology, 2021)
Background: Liver function and chronic inflammation influence the prognosis and surgical outcomes of many tumors. This study was performed to determine whether the Fibrosis-4 (FIB-4) index, originally defined as a noninvasive fibrosis marker, can predict the prognosis of gastric cancer in patients undergoing radical gastric cancer surgery. Methods: From patient data in our prospective database, we retrospectively analyzed 594 consecutive patients who underwent gastrectomy for gastric cancer. The FIB-4 index was calculated using laboratory data and age before gastrectomy. The clinical utility of FIB-4 was evaluated using the enumeration method. Patients were divided into two groups (high and low FIB-4 index), and overall survival (OS) was investigated. Cox analysis was used to identify independent parameters associated with prognosis. Finally, we developed a prognosis prediction model using the R statistical software. Results: A total of 556 patients were included, comprised 422 men and 134 women. Of these patients, 61 (11.0%) and 495 (89.0%) were classified into the low and high FIB-4 index groups, respectively. In addition to the indicators of FIB-4, preoperative age, tumor site, surgical procedure, TNM stage, and postoperative complications were independently predictive of prognosis (P < 0.05). The patients with a high FIB-4 index had significantly shorter OS (log-rank P = 0.01) than those with a low FIB-4 index. This association was also confirmed by multivariate analysis (hazard ratio 4.65, 95% confidence interval 1.07-4.29, P = 0.031). Conclusion: The present study showed that the preoperative FIB-4 index can predict long-term outcomes after gastrectomy for gastric cancer.